Food Innovation Adoption and Organic Food Consumerism—A Cross National Study between Malaysia and Hungary - Robert Jeyakumar Nathan; Soekmawati; Vijay Victor; József Popp; Mária Fekete-Farkas; Judit Oláh (Foods, 2021)
In order to meet the rising global demand for food and to ensure food security in line with the United Nation’s Sustainable Development Goal 2, technological advances have been introduced in the food production industry. The organic food industry has benefitted from advances in food technology and innovation. However, there remains skepticism regarding organic foods on the part of consumers, specifically on consumers’ acceptance of food innovation technologies used in the production of organic foods. This study measured factors that influence consumers’ food innovation adoption and subsequently their intention to purchase organic foods. We compared the organic foods purchase behavior of Malaysian and Hungarian consumers to examine differences between Asian and European consumers. The findings show food innovation adoption as the most crucial predictor for the intention to purchase organic foods in Hungary, while social lifestyle factor was the most influential in Malaysia. Other factors such as environmental concerns and health consciousness were also examined in relation to food innovation adoption and organic food consumerism. This paper discusses differences between European and Asian organic foods consumers and provides recommendations for stakeholders.